Tomato yellow leaf curl virus (TYLCV)-resistant tomatoes share molecular mechanisms sustaining resistance with their wild progenitor Solanum habrochaites but not with TYLCV-susceptible tomatoes. (June 2020) - Sade, Dagan; Sade, Nir; Brotman, Yariv; Czosnek, Henryk
Highlights: Solanum habrochaites (Sh) is a Tomato yellow leaf curl virus (TYLCV) resistant specie. Sh has been used as a source for TYLCV resistance breeding program to generate a TYLCV-resistant (R) and susceptible (S) tomato lines. R tomatoes share molecular mechanisms sustaining resistance with their wild genitor Sh but not with S tomatoes. Abstract: The wild tomato species Solanum habrochaites (Sh) has been used as a source for tomato yellow leaf curl virus (TYLCV) resistance in a breeding program to generate a TYLCV-resistant tomato line. Susceptible (S) and resistant (R) lines have been developed through this program. We compared the behavior of R, S and Sh tomato plants upon infection to find out whether the resistant phenotype of R plants originated from Sh. Results showed that mechanisms involving sugar-signaling (i.e., LIN6/HT1), water channels (i.e., TIP1;1), hormone homeostasis (i.e., ABA and SA) and urea accumulation were shared by S. habrochaites and R plants, but not by S. habrochaites and S tomatoes. This finding supports the hypothesis that these mechanisms were introgressed in the R genotype from the wild tomato progenitor during breeding for TYLCV resistance. Hence, identification of genes contributing to resistance to biotic stress from wild tomato species and their introgression into domestic plants ensures tomato supply and food security.